Pemanfaatan Tepung Pisang-Singkong Sebagai Alternatif Pengganti Tepung Terigu Pada Pembuatan Mie Dengan Penambahan Putih Telur atau Isolat Kedelai - Filiana Fizqi Utami; Zackiyah Zackiyah; Ali Kusrijadi (Jurnal Natural Scientiae, 2022)
In general, wheat flour noodles have a chewy and elastic texture, due to the presence of amylose, amylopectin and gluten proteins. People with celiac disease are gluten intolerant, so to enjoy noodles like people in general, an alternative gluten-free flour is needed to replace wheat flour, one of which is banana-cassava flour. To increase the nutritional value and texture of noodles, such as using wheat flour, egg white protein or soybean isolate and xanthan gum or ash water are added. This study aims to determine the effect of adding egg white protein or soybean isolate and the effect of xanthan gum or water ash on banana-cassava flour noodles on the physicochemical and sensory profiles. The research stages are the production of banana-cassava flour noodles, physicochemical profile analysis includes chemical profiles (moisture content, ash content and protein content), physical profile (optimum cooking time, swelling index, cooking loss and water absorption) and gluten content and sensory testing. The results of the analysis showed that the chemical profile of banana-cassava flour noodles met the wet noodle quality standard set by SNI 2987-2015, while the ash content was higher than the quality standard. Some good formulas, the water and ash content in the addition of egg white and xanthan gum (PTX) were around 4.95% and 1.80%, respectively, while the protein content in the addition of soybean isolate and water ash (PKA) was 12.89%. . Physical profiles for cooking time and swelling index on the addition of soybean isolate and water ash (PKA) were 2.50 minutes and 186.10%, respectively, cooking loss on the addition of egg white and xanthan gum (PTX) was 5.85%, while the water absorption in the addition of egg white and water ash (PTA) was 73.95%. Gluten levels in the addition of soybean isolates and water ash (PKA) ranged from 1.10%. The physicochemical profile of banana-cassava flour noodles was influenced by the type of protein and the best formula for gluten-free noodles was the addition of soy isolate. While the ash content, swelling index, water absorption, and gluten content are influenced by the type of agglomerate, and the best formulation for gluten-free noodles is the addition of ash water. The results of the organoleptic test obtained an average score of 4 (out of a scale of 5) on the attributes of color, aroma, taste, texture, and overall preference for the banana-cassava flour noodle sample.